Influence of pre and post-emergence herbicides in groundnut (Arachis hypogaea L.): INFLUENCE OF PRE AND POST-EMERGENCE HERBICIDES IN GROUNDNUT - P M VAGHASIA; V B BHALU; R H KAVANI (Journal of Oilseeds Research, 2014)
A field experiment was conducted at Main Oilseeds Research Station, Junagadh Agricultural University, Junagadh for three consecutive years during 2007-08 to 2009-10 to evaluate pre and post-emergence herbicides in rainy season groundnut. The experiment comprising nine weed control treatments of pre and post-emergence herbicides along with weedy check and weed free check was conducted in Randomised Block Design with three replications on medium clay soils with pH 7.9. The experimental field was infested with Echinochloa spp., Dinebra retroflexa, Digitaria sanguinalis, Indigofera glandulosa, Commelina benghalensis, Phyllanthus niruri, Euphorbia hirta, Digera arvensis, Cynodon dactylon, Tridax procumbens and Cyperus rotundus. Among the monocots and sedges, Echinochloa spp. and Cyperus rotundus were predominant. Complete weed free condition recorded highest dry pod, haulm and kernel yield (2773, 3934 and 1997 kg/ha, respectively). Among the herbicidal treatments, pendimethalin 1 kg/ha + quizalofop ethyl @ 50 g/ha at 20 days after sowing (DAS) recorded the lowest monocot (3.81/m2), dicot (3.63/m2), sedges (3.83/m2) weed density, dry weight of weeds (133 g/m2), weed control efficiency (84.2%) at 60 DAS and weed index (4.6%). The same treatment combination recorded significantly higher dry pod yield (2645 kg/ha), haulm yield (3424 kg/ha), kernel yield (1902 kg/ha), gross return (` 66360/ha), net return (`42190/ha) and B:C ratio (2.75).